Chronic osteomyelitis as evidence of a source of uncontrolled sepsis. A case report - Ariel Efrén Uriarte Méndez; Jorge L. Capote Padrón; José Julio Requeiro Molina; Lioby Kauteks Pardiñas de León (Medisur)
Sepsis and septic shock are major health problems that affect millions of people worldwide and have a high lethality. The infection source control is one of the fundamental aspects to achieve success in treatment. Once sepsis is suspected as a syndrome, all tests should be performed to identify the primary site of origin and the necessary specialist teams should be used. The objective of this work is to transmit the experiences derived from the care of an infant whose diagnosis of septic shock was made retrospectively when chronic osteomyelitis of the distal end of the right femur was discovered as a primary source of undiagnosed infection. The patient was admitted to the pediatric intensive care unit with multi-organ dysfunction. The diagnosis initially focused on acute viral myocarditis, but four weeks later osteomyelitis was diagnosed with chronicity criteria. The retrospective analysis ruled out the previous diagnosis and suggested acute osteomyelitis as the cause for septic shock, a clinical picture that began in a hidden way, but which almost compromised the patient's life. In the presence of a suspicious case of sepsis, the presence of a source of infection should be exhaustively searched. Given its frequency, acute hematogenous osteomyelitis should be taken into account.